2020
DOI: 10.1002/essoar.10501469.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trace metal fractional solubility in size-segregated aerosols from the tropical eastern Atlantic Ocean

Abstract: Soluble and total trace metals were measured in four size fractionated aerosol samples collected over the tropical eastern Atlantic Ocean. In samples that were dominated by Saharan dust, the size distributions of total iron, aluminum, titanium, manganese, cobalt, and thorium were very similar to one another and to the size distributions of soluble manganese, cobalt, and thorium. Finer particle sizes (<~3 μm) showed enhanced soluble concentrations of iron, aluminum, and titanium, possibly as a result of interac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…During our campaign Fe solubility was significantly higher in fine particles than coarse particles (paired t ‐test, P < 0.05, α = 0.05). Increase in Fe solubility with decrease in particle size has been observed at various locations around the globe by previous work (Baker et al., 2006b, 2020; Chen & Siefert, 2004; Fang et al., 2017; Gao et al., 2019, 2020; Johansen & Hoffmann, 2003; Longo et al., 2016; Ooki et al., 2009; Siefert et al., 1999), despite that different leaching protocols were employed to extract soluble Fe from collected ambient aerosol particles. Therefore, increase in Fe solubility with decrease in particle size may be a universal phenomenon, though one previous study (Buck, Landing, & Resing, 2010) found that Fe solubility did not increase with decreasing particle size for aerosol particles collected over the North Atlantic Ocean in June–August 2003.…”
Section: Resultsmentioning
confidence: 61%
“…During our campaign Fe solubility was significantly higher in fine particles than coarse particles (paired t ‐test, P < 0.05, α = 0.05). Increase in Fe solubility with decrease in particle size has been observed at various locations around the globe by previous work (Baker et al., 2006b, 2020; Chen & Siefert, 2004; Fang et al., 2017; Gao et al., 2019, 2020; Johansen & Hoffmann, 2003; Longo et al., 2016; Ooki et al., 2009; Siefert et al., 1999), despite that different leaching protocols were employed to extract soluble Fe from collected ambient aerosol particles. Therefore, increase in Fe solubility with decrease in particle size may be a universal phenomenon, though one previous study (Buck, Landing, & Resing, 2010) found that Fe solubility did not increase with decreasing particle size for aerosol particles collected over the North Atlantic Ocean in June–August 2003.…”
Section: Resultsmentioning
confidence: 61%
“…We adopt the most‐recent estimate from of S Th = 0.21 ± 0.07 Hayes et al (2017) derived from comparing aerosol settling fluxes of 232 Th with 250‐m integrated 232 Th d fluxes from the North Atlantic. We assume that thorium solubility remains constant with distance from dust source region, backed by a recent study finding that atmospheric processing of dust does not modify Th solubility in aerosols (Baker et al, 2020). For estimates of dust flux from particulate 230 Th‐ 232 Th, we also introduce a nominal 30% uncertainty typically assigned to the assumption that 230 Th flux through a depth horizon is equal to its water column production rate (Henderson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that we are assuming that S Fe / S Th remains constant during atmospheric dust transport. While Th solubility is constant during aerosol transport (Baker et al, 2020), Fe solubility generally increases with decreasing atmospheric dust loading (e.g., Sholkovitz et al, 2012). Thus, S Fe / S Th might be expected to increase with increasing distance from the dust source region.…”
Section: Discussionmentioning
confidence: 99%
“…Zn, Cd, Pb (Chance et al, 2015;Mahowald et al, 2018;Shelley et al, 2018)), or for metals whose solubility appears to be insensitive to atmospheric processing (e.g. Mn, Co (Baker et al, 2020)). The concentrations of the low solubility crustal metals (Fe, Al, Ti (Baker et al, 2020)) may be influenced by atmospheric processing.…”
Section: Seasonal Differencesmentioning
confidence: 99%
“…The size distribution and soluble fractions of metals in PM vary considerably between natural and anthropogenic sources. Many crustal elements occur predominantly in larger size fractions and have relatively low solubility, while anthropogenic metals tend to be associated with finer particles and have high soluble fractions (Mahowald et al, 2018;Baker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%